2020
DOI: 10.7759/cureus.9664
|View full text |Cite
|
Sign up to set email alerts
|

Extended Dwell Time Improves Results of Fibrinolytic Therapy for Complex Pleural Effusions

Abstract: Introduction Published trials of intrapleural therapy for complex pleural effusions rely on fibrinolytics and deoxyribonuclease (DNase) with dwell times of less than six hours and frequent dosing. We reviewed our experience with fibrinolytics alone but with a longer dwell time (12 hours). Methods Tissue plasminogen activator (tPA, 1-6 mg per dose) was given through pigtail catheters placed using image guidance. Planned treatment was for a dwell time of 12 hours with repeat dosing daily for three days or until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In these patients effusion drainage was surprisingly brisk, leading us to modify our treatment regimen to the use of tPA alone with a prolonged dwell time. In reviewing that early experience we concluded that a 4 mg dose of tPA was sufficient, and that a 12 h dwell time was most effective [ 12 ]. In this report we review our experience with that standardized protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients effusion drainage was surprisingly brisk, leading us to modify our treatment regimen to the use of tPA alone with a prolonged dwell time. In reviewing that early experience we concluded that a 4 mg dose of tPA was sufficient, and that a 12 h dwell time was most effective [ 12 ]. In this report we review our experience with that standardized protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The serendipitous result was the discovery that tPA alone with a longer dwell time seemed effective. In a review of our experience treating 47 effusions in 46 patients with tPA alone, in doses ranging from 1 to 6 mg and dwell times ranging from 5 to 14 h, we found that only 6% required surgery [ 12 ]. Based on this review we concluded that a once daily dose of 4 mg with a dwell time of 12 h seemed most effective and most easily administered.…”
Section: Introductionmentioning
confidence: 99%
“…In these patients effusion drainage was surprisingly brisk, leading us to modify our treatment regimen to the use of tPA alone with a prolonged dwell time. In reviewing that early experience we concluded that a 4 mg dose of tPA was su cient, and that a 12 hour dwell time was most effective 12 . In this report we review our experience with that standardized protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The serendipitous result was the discovery that tPA alone with a longer dwell time seemed effective. In a review of our experience treating 47 effusions in 46 patients with tPA alone, in doses ranging from 1 to 6 mg and dwell times ranging from 5 to 14 hours, we found that only 6% required surgery 12 . Based on this review we concluded that a once daily dose of 4 mg with a dwell time of 12 hours seemed most effective and most easily administered.…”
Section: Introductionmentioning
confidence: 97%
“…Tissue plasminogen activator (tPA) is a fibrinolytic that has been shown to be effective for drainage of loculated pleural effusions [10][11][12]. Based on our favorable experience with intrapleural tPA for management of complex pleural effusions [13], we started using it to eliminate loculated collections that developed after pleurodesis. To the best of our knowledge, this had not been attempted before.…”
Section: Introductionmentioning
confidence: 99%